How Relevant Is Infrastructure to Growth in East Asia? - Seethepalli, Kalpana; Bramati, Maria Caterina; Veredas, David (World Bank, Washington, DC, 2012)
This paper seeks to shed some light on the extent to which infrastructure sub-sectors - energy, telecommunications, water supply, sanitation, and transport - contributed to growth in East Asia during 1985-2004. It also attempts to provide additional insights on whether the relationship between infrastructure and growth depends on five additional variables: the degree of private participation in infrastructure, the quality of governance, the extent of rural-urban inequality in access to infrastructure services, country income levels, as well as geography. The findings show that greater stocks of infrastructure were indeed associated with higher growth. However, a more nuanced look at the sensitivity of infrastructure impacts on the five additional variables yields different results, with some sectors supporting conventional expectations and others yielding mixed or counter-intuitive results. In particular, the telecom and sanitation sectors yield statistically significant results supporting the a priori hypotheses; electricity and water infrastructure provide mixed results; and road infrastructure consistently contradicts a priori expectations. The results are consistent with the widely-accepted idea in policy research that infrastructure plays an important role in promoting growth, as well as with the viewpoint that certain countries' endowments influence the growth-related impacts of infrastructure.